RNA Drug Delivery Using Biogenic Nanovehicles for Cancer Therapy - Li, Nuannuan; Sun, Yiying; Fu, Yuanlei; Sun, Kaoxiang (Frontiers in Pharmacology, 2021)
RNA-based therapies have been promising method for treating kinds of diseases, and four siRNA-based drugs and two mRNA-based drugs have been approved on market now. However, none of them is applied for cancer treatment. This is not only because of the complexity of tumor microenvironment, but also due to the intrinsic obstacles of RNAs. Till now, kinds of strategis have been developed to improve the performance of RNAs for cancer therapy, especially the nanoparticles-based ones using biogenic materials. They are much more compatible with less toxicity compared to the ones using synthetic polymers, and the most widely studied biogenic materials are oligonucleotides, exosomes and cell membranes. The particular characteristics make them show different capacity in internalization and endosomal escape as well as specific targeting. In this paper, we systematacially summary the RNA-based nano-delivery systems using biogenic materials for cancer therapy, and we believe this review will provide a valuable reference for researchers involved in the field of biogenic delivery and RNA-based therapies for cancer treatment.